Toward A General Theory of Consumer Motivation: A Critical Review - Simamora, Bilson (Technium Social Sciences Journal, 2021)
Consumer motivation has been known long as a marketing concept. However, most of its concepts still belong to other fields, and there is little effort has been incurred to define and model them in the context of typical consumer behavior. This study aims to overcome this theoretical gap. Therefore, the author narrates consumer motivation history and critically offers a new definition and flexible and unstructured model through which context-specific models can depart. This study exerts that the motivation theory goes into a more diverse direction caused by the distinctive nature of consumer behavior nature and contexts. For that reason, the consumer motivation model should give the spaces in which a specific model for particular behavior can be developed. The study’s loose and unstructured model is found as able to take that function. Further studies can utilize this model in studying motivation to perform or not perform particular consumption behavior in a specific context.